Phycocyanin Improves Reproductive Ability in Obese Female Mice by Restoring Ovary and Oocyte Quality - Wen, Xin; Han, Zhe; Liu, Shu-Jun; Hao, Xin; Zhang, Xiao-Jie; Wang, Xing-Yue; Zhou, Cheng-Jie; Ma, Yu-Zhen; Liang, Cheng-Guang (Frontiers in Cell and Developmental Biology, 2020)
Reproductive dysfunction associated with obesity is increasing among women of childbearing age. Emerging evidence indicates that maternal obesity impairs embryo development and offspring health, and these defects are linked to oxidative stress in the ovary and in oocytes. Phycocyanin (PC) is a biliprotein from Spirulina platensis that possesses antioxidant, anti-inflammatory, and radical-scavenging properties. Our previous studies have shown that PC can reduce reactive oxygen species (ROS) accumulation in oocytes in D-gal-induced aging mice. Here, Institute of Cancer Research (ICR) mice fed a high-fat diet (HFD) to model obesity was used to test the effect of PC on reversing the fertility decline caused by obesity. We observed a significant increase in litter size and offspring survival rates after PC administration to obese mice. Further, we found that PC not only ameliorated the level of ovarian antioxidant enzymes, but also reduced the occurrence of follicular atresia in obese female mice. In addition, the abnormal morphology of the spindle-chromosome complex (SCC), and the abnormal mitochondrial distribution pattern in oocytes, both recovered. The obesity-related accumulation of ROS, increased number of early apoptotic cells, and the abnormal expression of H3K9me3 in oocytes were all partially reversed after PC administration. In summary, this is the first demonstration that PC can improve fertility by partially increasing ovarian and oocyte quality in obese female mice and provides a new strategy for clinically treating obesity-related infertility in females.